Effectiveness of preemptive analgesia on postoperative pain following third molar surgery: Review of literatures - Akira Yamaguchi; Kimito Sano (Elsevier, 2013)
We investigated the efficacy of preemptive analgesia for mandibular third molar surgery by, reviewing of randomized controlled trials. In many of the studies, the preemptive use of NSAIDs before, tooth extraction demonstrated that the postoperative pain was better controlled beyond the expected, effect time, compared without such preemptive use. On the other hand, some studies reported that, compared to the administration before removal of the tooth, postoperative administration was, associated with better suppression of postoperative pain. This suggests that in postoperative pain after, removal of mandibular third molars, peripheral sensitization caused by reactive inflammation, following the tooth extraction and secondary central sensitization are more important factors than, direct central sensitization caused by surgical tissue damage. Accordingly, when a mandibular third, molar is removed, central sensitization due to tissue damage should be suppressed by, preadministration of analgesics. In order then to suppress postoperative peripheral sensitization, the, readministration of analgesics is considered more effective. Furthermore, although acid NSAIDs are, effective analgesics, the associated adverse events are of concern. Accordingly, acetaminophen (1000 mg), which, is devoid of anti-inflammatory effects but is a weak cyclooxygenase inhibitor, can be used for, preemptive analgesia administration.